THE TRANSITION FROM THE NEOCLASSICAL GROWTH MODEL TO ECOLOGY - SCHLAUCH, Michael; PALMISANO, Gaia (Journal of Environmental Management and Tourism; Vol 4 No 1 (2013): JEMT Volume IV Issue 1(7) Summer 2013, 2016)
This paper examines the assumptions and conclusions of the neoclassical growth model put forth by Solow and many others. We investigate the origins of the paradigm of unlimited growth and technological progress and question their plausibility. In contrast, we develop a modified version of the neoclassical growth model where we consider non-human, environmental resources such as energy as an additional input factor and recognize their limited capacity to recover from human impact. Surprisingly, the same mathematical framework of the neoclassical growth model gets to the opposite conclusions - namely that long term growth cannot exceed a level in which nature begins to deplete. Growth further that level as we might experience today leads to natural and economic disaster. Technological progress understood as productivity increase can only delay but not prevent this crisis. We compare these conclusions to the opposite hypothesis of the Environmental Kuznets Curve. Also we show how this model can lead to a greater understanding of present or future observations that are connected to environmental deficiency, such as social divergence and stagnating life satisfaction in developed countries.
Keywords: growth, degrowth, limits of growth, ecological economics, neoclassical growth model, environmental Kuznets curve